Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 10 - Review - Page 747: 62



Work Step by Step

$\frac{\sqrt[4] {a^{6}b^{13}}}{\sqrt[4] {a^{2}b}}$ =$\sqrt[4] \frac{a^{6}b^{13}}{a^{2}b}$ =$\sqrt[4] {a^{6-2}b^{13-1}}$ =$\sqrt[4] {a^{4}b^{12}}$ =$(a^{4})^{\frac{1}{4}}\times(b^{12})^{\frac{1}{4}}$ =$a\times b^{3}$ =$ab^{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.